Cardiovascular risk factors prevalence in adolescents in educational institutions - Sáez, Yeny (2009)
Objectives: To determine the prevalence of cardiovascular risk factors (CRF) in adolescents. Design: Descriptive and cross-sectional, multistage random sampling. Setting: Twelve state secondary schools, district of San Juan de Lurigancho, Lima-Peru. Participants: Adolescents. Interventions: We studied a sample of 277 adolescents 12 to 17 years old, 49,1% male, during August and November 2007. CRF studied were systolic / diastolic hypertension (≥95p by age, sex and height), dyslipidemia (hypercholesterolemia ≥200 mg /dL, hypertriglyceridemia ≥130 mg/dL, high LDL-c ≥130 mg/dL and low HDL-c <40mg/dL), smoking, sedentary lifestyle, obesity/abdominal obesity (body mass index ≥ 95p and waist circumference ≥90p by age and sex), inadequate diet, impaired fasting glucose (≥110 mg/dL) and family history of cardiovascular disease (CVD). Blood pressure measurement, anthropometric data and biochemical analysis were performed according to international recommendations. Smoking prevalence, sedentary lifestyle, unhealthy diet and family history of cardiovascular disease were determined by previously validated questionnaires. Main outcome measures: Cardiovascular risk factors prevalence. Results: Hypertension, smoking, sedentary lifestyle, obesity, unhealthy diet and family history of CVD prevalence were respectively 1,5%, 35%, 62,8%, 7,6%, 41% and 19,1%. Dyslipidemia (determined in a 39 adolescents subsample) was prevalent (85%) due mainly to low HDL-c levels (76,9%), high LDL-c levels (28,2%), hypertriglyceridemia (17,9%) and hypercholesterolemia (7,7%). No adolescent showed fasting blood sugar alteration. Conclusions: CRFs prevalence and/or frequency in adolescents surveyed suggest the need for intervention programs that modify lifestyle in order to prevent cardiovascular disease in adulthood.